Do speculators drive crude oil prices? Dispersion in beliefs as a price determinant - Jochen Möbert (Deutsche Bank Research, 2009)
This article discusses the influence of speculators in the futures market on crude oil prices. The results suggest the dispersion in beliefs influences both crude oil prices and price volatility.
Keywords: C51; G12; G18; Q41; 330; crude oil market; futures market; speculation; Ölpreis; Volatilität; Rohstoff-Futures; Wertpapierspekulation; Erwartungstheorie; Schätzung; USA